Weínmannía spp. (Cunoniaceae): Fitoquímica básica - Gómez P, Luis Diego (Universidad de Costa Rica, 1995)
A preliminary study on the phytochemistry of Wrinmannia (Cunoniaceae) and its pharmacological potential suggests important uses related with the male genitourinary system.